Effect of IBA on Rooting Behaviour of Melia dubia Cuttings - Swathi, Shedage; Gupta, Garima; Singh, Shashwat; Bhukya, Rajesh (Indian Forester, 2025)
This study investigated the effects of varying concentrations of Indole-3-butyric acid (IBA) on the sprouting, rooting, and biomass of Melia dubia cuttings. Softwood and semi-hardwood cuttings were treated with IBA concentrations of 400, 800, 1200, and 1600 ppm, with untreated cuttings serving as controls. Results indicated that IBA significantly enhanced the sprouting time, number of cuttings sprouted, survivability, and shoot and root development. The 1200 ppm IBA treatment (T3) demonstrated the fastest sprouting time of 6.17 days, the highest number of sprouts (11.5), and the greatest shoot length (20.5 cm). Softwood cuttings (S2) outperformed semi-hardwood cuttings (S1), particularly when combined with higher IBA concentrations. The combination of 1600 ppm IBA with softwood cuttings (T4S2) achieved the quickest sprouting time (4.3 days) and the highest number of sprouts (14). Root development was most substantial in cuttings treated with 1200 ppm IBA, showing a root length of 13.5 cm and 63 roots per cutting. Biomass accumulation was also highest in cuttings treated with 1200 ppm IBA, with a fresh shoot weight of 12.9 grams and a dry shoot weight of 7.57 grams. These findings underscore the critical role of IBA in enhancing the propagation success of Melia dubia cuttings.